Meningkatkan Kemampuan Kelembagaan Untuk Mendukung Pembangunan Kualitas Manusia: Suatu Perspektif Administrasi Negara - Sofian Efendi (Magister Administrasi Publik, 1996)
The objective of the national development in, the Second Long Term Development Plan (PIPT II), besides striving to achieve economic growth, is also intended to continuously develop the human resources and the natural resources ia an effort to improve on the human value. The orientation of this development which has now changed, requi/ es an odministrative system which is fundamentally Offerent from the system which is currently operational. This writing will advance a precise ahentative thought about the institutional per spective.for the development of Inunwi quality by examining the form of bureaucracy which is uecessaty for national development, which in a way. is intended to improve on the human value, and the quality of society as a whole, which is necessaiyfor this kind ofbureaucrac..y. In other to attain the means as it was earlier on portrayed, then this development of human quality must be able to provide an opportunity.for the community to participate in every development activity. In this case, the other major prerequisite is the necessity to reorientate the bureaucracy which, is snore organic-adaptive in nature. This reorientation covers the .function, the structure and the procedure of the operating system of development administration from providers of public se/vices directly towards the direction of the creation of self sustenance and the ability of an area and the community in fuljilling their own requirements.